Missed potential? The role of migrant entrepreneurs in shaping Germany's future economy - Mathilde Haufe; Hanna Hottenrott; Elisa Rodepeter; Eline Schoonjans (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
Entrepreneurship is essential for innovation and economic growth. Newly founded companies contribute to innovation and technology diffusion and increase pressure on incumbent firms to innovate. In Germany, migrant entrepreneurs play an increasingly important role in the entrepreneurial landscape. Their integration into this ecosystem is not only essential for fostering inclusive economic growth, but migrant founders also display a comparatively higher propensity for innovation. Based on data and insights from the IAB/ZEW Start-up Panel, this policy brief highlights the characteristics of and challenges for migrant entrepreneurs to understand how future policy frameworks could be designed to make better use of their potential. We find that while young migrant-founded firms are often opportunity-driven, have high growth ambitions, and are innovative, they are constrained in their access to external capital and have to rely more frequently on their founders' and their families' resources. These findings suggest that frictions in financing young firms hamper migrant entrepreneurship in Germany and that there is room to address these constraints through targeted policies facilitating access to support programmes and bank financing.
Keywords: 330